Housing mobility protects against alcohol use for children with socioemotional health vulnerabilities: An experimental design. (19th September 2022) - Thyden, Naomi H.; Schmidt, Nicole M.; Joshi, Spruha; Kim, Huiyun; Nelson, Toben F.; Osypuk, Theresa L.
Abstract: Purpose: Neighborhood context may influence alcohol use, but effects may be heterogeneous, and prior evidence is threatened by confounding. We leveraged a housing voucher experiment to test whether housing vouchers' effects on alcohol use differed for families of children with and without socioemotional health or socioeconomic vulnerabilities. Trial design: In the Moving to Opportunity (MTO) study, low‐income families in public housing in five US cities were randomized in 1994 to 1998 to receive one of three treatments: (1) a housing voucher redeemable in a low‐poverty neighborhood plus housing counseling, (2) a housing voucher without locational restriction, or (3) no voucher (control). Alcohol use was assessed 10 to 15 years later (2008 to 2010) in youth ages 13 to 20, N  = 4600, and their mothers, N  = 3200. Methods: Using intention‐to‐treat covariate‐adjusted regression models, we interacted MTO treatment with baseline socioemotional health vulnerabilities, testing modifiers of treatment on alcohol use. Results: We found treatment effect modification by socioemotional factors. For youth, MTO voucher treatment, compared with controls, reduced the odds of ever drinking alcohol if youth had behavior problems (OR = 0.26, 95% CI [0.09, 0.72]) or problems at school (OR = 0.46, [0.26, 0.82]). MTO low‐poverty treatment (vs. controls) also reduced the number of drinks if their health required special medicine/equipment (OR = 0.50 [0.32, 0.80]). Yet treatment effects were nonsignificant among youth without socioemotional vulnerabilities. Among mothers of children with learning problems, MTO voucher treatment (vs. controls) reduced past‐month drinking (OR = 0.69 [0.47, 0.99]), but was harmful otherwise (OR = 1.22 [0.99, 1.45]). Conclusions: For low‐income adolescents with special needs/socioemotional problems, housing vouchers protect against alcohol use. Abstract : In the 1990's the Moving to Opportunity study randomized low‐income families to receive housing vouchers vs staying in public housing. For low‐income adolescents with special needs/socioemotional problems at baseline, housing vouchers protected against alcohol use 10‐15 years later.